Pontes que se estabelecem em educação sexual: um diálogo sobre a formação continuada e os saberes das práticas pedagógicas de professoras no Brasil e em Portugal - Santos, Vera Márcia Marques (Universidade do Vale do Rio dos Sinos, 2011)
The purpose of this investigation was to study the continuous training of sexual educator teachers aimed to understand the formative path of Brazilian and Portuguese teachers in engaging with the themes sexuality and sex education; to analyse the conceptions and teacher knowledge about the sexual manifestations or sexuality that occur in the educational field in which they work; to understand how teachers have made their pedagogical interventions towards the manifestations of sexuality in children, adolescents and adults. To this end, the field research was based on the assumptions of qualitative research was conducted with fourteen teachers. Nine in the process of continuing education and five trainers, from Brazil and Portugal. Three instruments were used for data collection: Dialogical Group and questionnaire for the teachers in the process of continuing education, and semi-structured interviews with the trainer teachers, whose writings formed the theoretical support for the raising ideas. We started from the proposition that the knowledge that has referenced the pedagogical practices of teachers and professors have been their own intuition and sensitivity to situations involving sexuality, and very little has come from training institutions, although continuing education is a powerful alternative to enable qualification for the teaching practice. Among the main theoretical references supporting this research we have: Nóvoa (1995; 2000; 2002; 2005), Freire (1974, 1978, 1980, 1982, 1985, 1987, 1992, 1996, 1997, 2001, 2006, 2006b, 2009), Pimenta (1999; 2002), Tardif (2007), Garcia (2000), Figueiró (1996; 2006; 2007; 2009; 2009b), Streck; Redin e Zitkoski (2008), Arroyo (2002; 2004; 2008), Melo e Pocovi (2002), Nunes (1996, 1997, 2006) e Ribeiro (1990; 2004). Data analysis was based on the content analysis, supported by Laurence Bardin (2000), where the dimensions that appeared in the research participants speech were contemplated. It is concluded that teacher training can not be considered as an isolated task, disconnected from the reality in which these teachers work, the training courses need to be more than the place for the acquisition of techniques and knowledge - the teacher training is the key moment of socialization and professional setting, and further, that the professional learning of teaching is related to the experiences that go through the motions of life that constitute teachers as subjects, considering the history of each one.
Keywords: Formação de professoras; Sexualidade e educação sexual; Saberes e práticas pedagógicas; Formação continuada; Educação sexual emancipatória; Formación de profesores; Sexualidad y educación sexual; Conocimientos y prácticas pedagógicas; Educación continua; Educación sexual y emancipación; Teachers trainning; Sexuality and sex education; Knowledge and pedagogical practices; Continuing education; Emancipation sex education; ACCNPQ::Ciências Humanas::Educação